Spiritual Addiction: Searching for Love in a Coldly Indifferent World - Wyner, Garret B. (Religions, 2022)
I describe "spiritual" addiction as a felt compulsion to seek surrogates in the absence of that spirit of unconditional love underlying core personality change. We awaken to a "real" world akin to a prison in which all sides seem morally compromised, so any choice seems to necessitate sacrificing our conscientious relationship to the truth. Thus, spiritual addiction runs deeper than physical and psychological addictions to include socially accepted "addictions" to all we associate with "success"—including our morality and religion. All that we seek may be grounded in a collectively imbibed prejudice toward truth itself. If so, such a prejudice, underlying spiritual addiction, compromises our will, reason, feelings, actions, and character—including all of our relationships. It underlies the reality of a collective moral crisis which, we show, is more deeply a religious crisis tempting us to doubt the reality and attainability of that unconditional love that provides a foundation for hope. To overcome the prejudice underlying spiritual addiction, we show how unconditional love can be realized by placing conscientiousness in the foreground of concern as we are guided by the most reliable moral and spiritual witnesses in our history distinct from any religious group claiming to speak in their name.